Amine-Functionalized Mesoporous Silica SBA-15 for Enhanced Solubility and Release Rate of Gliclazide - Sayyidina, Fasqina; Gumala, Azhoma; Zaini, Erizal; Hanifa, Dini; Hasanah, Uswatul (Science and Technology Indonesia, 2025)
Gliclazide (GLI), a sulfonylurea-class antidiabetic drug, exhibits poor aqueous solubility, limiting its bioavailability. This study aimed to enhance gliclazide’s solubility and dissolution rate by adsorbing it into mesoporous silica SBA-15 and amine-functionalized SBA-15 (SBA-15-A). SBA-15 was synthesized using Pluronic® P123 as a template and tetraethyl orthosilicate (TEOS) as the silica precursor, while 3-aminopropyltriethoxysilane (APTES) was used to introduce amine functional groups. Gliclazide was loaded into SBA-15 and SBA-15-A at a 1:3 mass ratio. The materials (GLI, SBA-15, SBA-15-A, GLI-SBA, and GLI-SBA-A) were characterized using nitrogen adsorption-desorption isotherms, differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and powder X-ray diffraction (PXRD). Characterization revealed that the pore diameters of SBA-15 and SBA-15-A were 6.079 nm and 5.483 nm, respectively. FT-IR confirmed the interaction between gliclazide and the mesoporous carriers. SEM and TEM analysis showed crystalline gliclazide and rod-shaped morphologies for the mesopores samples. DSC and PXRD results indicated that most of the gliclazide had been converted to an amorphous form. Solubility testing over 24 hours showed that GLI-SBA and GLI-SBA-A improved gliclazide solubility by 1.375- and 2.334-fold, respectively, compared to pure gliclazide. Dissolution testing in distilled water revealed a 6.033-fold and 3.887-fold increase in the release rate at 5 minutes for GLI-SBA and GLI-SBA-A, respectively. Both solubility and release rate improvements were statistically significant (p <0.05). These findings suggest that amine functionalization of SBA-15 effectively enhances the solubility and dissolution rate of gliclazide.